2008
DOI: 10.1074/jbc.m710011200
|View full text |Cite
|
Sign up to set email alerts
|

Cdc28 and Cdc14 Control Stability of the Anaphase-promoting Complex Inhibitor Acm1

Abstract: The anaphase-promoting complex (APC) regulates the eukaryotic cell cycle by targeting specific proteins for proteasomal degradation. Its activity must be strictly controlled to ensure proper cell cycle progression. The co-activator proteins Cdc20 and Cdh1 are required for APC activity and are important regulatory targets. Recently, budding yeast Acm1 was identified as a Cdh1 binding partner and APC Cdh1 inhibitor. Acm1 disappears in late mitosis when APC Cdh1 becomes active and contains conserved degron-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 59 publications
3
58
0
Order By: Relevance
“…C283S has previously been used as a substrate trap to capture the complexes formed between Cdc14p and its cognate phospho-substrates (Hall et al, 2008). We found that Orc2p, Orc6p and Mcm3p could be co-immunoprecipitated with FLAGCdc14 C283S , but not wild-type FLAG-Cdc14p, expressed from the GAL1 promoter to override the sequestration of Cdc14p by its inhibitors in mitotic cells (Fig.…”
Section: The Pre-rc Components Orc2p Orc6p Cdc6p and Mcm3p Are Subsmentioning
confidence: 79%
See 2 more Smart Citations
“…C283S has previously been used as a substrate trap to capture the complexes formed between Cdc14p and its cognate phospho-substrates (Hall et al, 2008). We found that Orc2p, Orc6p and Mcm3p could be co-immunoprecipitated with FLAGCdc14 C283S , but not wild-type FLAG-Cdc14p, expressed from the GAL1 promoter to override the sequestration of Cdc14p by its inhibitors in mitotic cells (Fig.…”
Section: The Pre-rc Components Orc2p Orc6p Cdc6p and Mcm3p Are Subsmentioning
confidence: 79%
“…We then used a well-established in vitro Cdc14p phosphatase assay (Visintin et al, 1998;Jaspersen and Morgan, 2000;Pereira et al, 2002;Bloom and Cross, 2007;Hall et al, 2008;ClementeBlanco et al, 2009) to test whether Cdc14p is able to dephosphorylate the initiation proteins in vitro. Orc2p, Orc6p, Cdc6p and Mcm3p isolated from mitotic cells were efficiently dephosphorylated in vitro when they were incubated with recombinant GST-tagged Cdc14 (GST-Cdc14) (Fig.…”
Section: C283smentioning
confidence: 99%
See 1 more Smart Citation
“…36 The degradation of Swe1 itself may be at least partially APC-dependent. 37 Thus, one possibility is that following Acm1 degradation initiated in early anaphase, 8,9,12 Cdh1 is recruited to the bud neck via the high affinity interaction with its substrate Hsl1. This specific localization could then allow the rapid, efficient and coordinated clearance of several key Cdh1 substrates once APC Cdh1 is activated by the mitotic exit network and Cdc14-catalyzed Cdh1 dephosphorylation.…”
Section: Methodsmentioning
confidence: 99%
“…We conclude that Cdc28 likely regulates Acm1 stability by direct phosphorylation and that these four phosphorylation sites have additive effects on Acm1 stability in vivo. While this report was under review, Hall et al also reported a role for Thr-161 phosphorylation in stabilizing Acm1 (26), though they did not examine the other single-point mutations.…”
Section: Cdh1mentioning
confidence: 97%